VideoPal: An Asynchronous Video Based Communication System - Inkpen, Kori; Du, Honglu; Roseway, Asta; Hoff, Aaron; Johns, Paul; Meyers, Brian; Czerwinski, Mary; Chorianopoulos, Konstantinos; Gross, Tom; Ljungstrand, Peter (Demo at CSCW 2011, 2011)
This paper describes VideoPal, a novel video based asynchronous communication system. VideoPal is currently being used by approximately 30 4th and 5th grade students from the US and Greece to explore the opportunities and challenges of video-mediated asynchronous communication in supporting traditional Pen Pal activities.